2006
DOI: 10.1111/j.1365-3040.2006.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of nitrate reductase in the psychrophilic unicellular alga Koliella antarctica and the mesophilic alga Chlorella sorokiniana

Abstract: Temperature responses of nitrate reductase (NR) were studied in the psychrophilic unicellular alga, Koliella antarctica , and in the mesophilic species, Chlorella sorokiniana . Enzymes from both species were purified to near homogeneity by Blue Sepharose (Pharmacia, Uppsala, Sweden) affinity chromatography and high-resolution anionexchange chromatography (MonoQ; Pharmacia; Uppsala, Sweden). Both enzymes have a subunit molecular mass of 100 kDa, and K. antarctica NR has a native molecular mass of 367 kDa. NR fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…NJ-10 and NJ-17 exhibited the maximum activity at 20°C in vitro, with 15 and 26 nmol NO 2 -min -1 mg -1 protein, respectively, while the maximum activity of nitrate reductase was found at 25°C with a value of 13 nmol NO 2 -min -1 mg -1 protein in FACHB753. Our results indicate that the two Antarctic algae, especially NJ-17, which shows a high level of nitrate reductase specific activity, share same properties which are typical of coldadapted organisms (Feller and Gerday 1997;Vona et al 2004;Di Martino Rigano et al 2006).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…NJ-10 and NJ-17 exhibited the maximum activity at 20°C in vitro, with 15 and 26 nmol NO 2 -min -1 mg -1 protein, respectively, while the maximum activity of nitrate reductase was found at 25°C with a value of 13 nmol NO 2 -min -1 mg -1 protein in FACHB753. Our results indicate that the two Antarctic algae, especially NJ-17, which shows a high level of nitrate reductase specific activity, share same properties which are typical of coldadapted organisms (Feller and Gerday 1997;Vona et al 2004;Di Martino Rigano et al 2006).…”
Section: Resultssupporting
confidence: 58%
“…Many concerns have been concentrated on the polar psychrophiles and few reports on the psychrotolerants can be found. In comparison with mesophiles, the content of the poly-unsaturated and short chain fatty acids in the membrane lipid is much higher, the optimal enzyme activity of nitrate reductase, glutathione reductase, argininosuccinate lyase shifts toward lower temperatures and rates of photosynthesis and respiration show a higher value in polar psychrophiles (Vona et al 2004;Di Martino Rigano et al 2006;Morgan-Kiss et al 2006;Ding et al 2007). In contrast, Morgan-Kiss et al (2008) found that the composition of the membrane lipid in psychrophilic Chlorella BI was similar to that in mesophilic one and no short chain fatty acids were detected.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae from this region can grow at low temperatures close to the freezing point (Morgan-Kiss et al 2006), depending on the synthesis of polyunsaturated fatty acids (Mock & Kroon 2002a, b;Morgan-Kiss et al 2002), cold-adapted nitrate reductase (Vona et al 2004;Di Martino Rigano et al 2006), and possibly the production of NO (Estevez & Puntarulo 2005). Compared to studies of their growth at low temperature, the antifreeze mechanisms of Antarctic microalgae are little known.…”
Section: Introductionmentioning
confidence: 99%
“…5d). The characteristics of NR from various algae belonging to different thermal habitat showed a wide range of temperature adaptation (Di Martino Rigano et al 2006). It is reported that the active centre of the enzyme gets structurally altered to shift the enzyme activity optimum to the region of higher temperatures and increased the thermal stability of the NR (Morozkina and Zvyagilskaya 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased enzyme activity at lower temperature may be due to the fact that the affinity for the substrate is greatly decreased at lower temperature (Reay et al 1999). Di Martino Rigano et al (2006) reported that NR enzyme from the psychrophilic algae Koliella antarctica possesses structural modifications that make it colder adapted, being more catalytically efficient at lower temperatures, but they are less thermally stable than NR from mesophilic Chlorella sorokiana simultaneously.…”
Section: Resultsmentioning
confidence: 99%